Biathlon diagnostics workshop - Dirnberger, J.; Sattlecker, G.; Wiesinger, H.-P.; Birklbauer, J.; Buchecker, M. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
Biathlon is a physically, mentally, and technically challenging winter sport that combines cross-country skiing with rifle shooting. The competition results are based on skiing time, shooting time, and shooting performance. Depending on the race format (sprint, individual, pursuit, and mass start), studies have revealed that shooting performance may explain ~30-50% of overall biathlon performance 1-4. Since almost two decades now the Department of Sports and Exercise Science of the University of Salzburg and the Olympic Training Center Salzburg offers biathlon shooting diagnostics. In 2022 alone, more than 70 national and international athletes took advantage of this offer. The aim of the workshop is to give attendees a practical insight into our diagnostics. Our diagnostics include both prone and standing shooting, by default in a rested state, but if desired also in a physically stressed state (ergometer or roller skis). Athletes are instructed to shoot at their normal competition rhythm and technique. We employ a range of measurement tools: Body sway during shooting is quantified using a 2-part force platform (University of Salzburg, Salzburg, Austria). A strain gauge force transducer (oil sensor) (Spezialmesstechnik Ilmenau, Ilmenau, GER) installed on the trigger serves to measure trigger behaviour. Rifle stability/aiming point trajectory is evaluated using an Noptel ST 2000 Sport training device (Noptel, Oulu, FIN). The device consists of an optical transmitter-receiver unit attached to the barrel of the gun and a reflector attached around the target. A pad fastened to the back of the rifle stock is used to measure the pressure between rifle stock and shoulder (Novel GmbH, Munich, GER). A load cell (Futek, Irvine, US) serves to determine the tension on the sling. Shooting scores are recorded by the computer-controlled display system Meyton MF5R1 (Meyton Electronics, Melle-Bruchmühlen, GER). An accelerometer (Biovison, Wehrheim, GER) mounted on the barrel of the gun serves to detect the shot event to retrospectively synchronize the data. All data run together in a custom-made software (IKE-Software Solutions, Salzburg, AUT), with which data are synchronized, further processed and reported. Finally, athletes get a personalized strengths-weaknesses profile based on normative values and recommendations to improve their shooting performance. Our longstanding experience shows that regular biomechanical testing using our setup is particularly beneficial for younger athletes.